2006
DOI: 10.1091/mbc.e05-06-0585
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Screen for Petite-negative Yeast Strains Yields a New Subunit of the i-AAA Protease Complex

Abstract: Unlike many other organisms, the yeast Saccharomyces cerevisiae can tolerate the loss of mitochondrial DNA (mtDNA). Although a few proteins have been identified that are required for yeast cell viability without mtDNA, the mechanism of mtDNA-independent growth is not completely understood. To probe the relationship between the mitochondrial genome and cell viability, we conducted a microarray-based, genomewide screen for mitochondrial DNA-dependent yeast mutants. Among the several genes that we discovered is M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 86 publications
(115 reference statements)
7
94
1
Order By: Relevance
“…It has been previously reported that S. cerevisiae does not tolerate loss of mtDNA combined with activation of the cAMP-PKA pathway by IRA2 or PDE2 deletion (Dunn et al 2006). Our analysis demonstrates that activation of the pathway by BCY1 deletion is tolerated in rich growth media, but not under starvation conditions with additional stress.…”
Section: (D-g) Error Bars Indicate Standard Deviations Of Three Indepsupporting
confidence: 47%
See 1 more Smart Citation
“…It has been previously reported that S. cerevisiae does not tolerate loss of mtDNA combined with activation of the cAMP-PKA pathway by IRA2 or PDE2 deletion (Dunn et al 2006). Our analysis demonstrates that activation of the pathway by BCY1 deletion is tolerated in rich growth media, but not under starvation conditions with additional stress.…”
Section: (D-g) Error Bars Indicate Standard Deviations Of Three Indepsupporting
confidence: 47%
“…It has been reported that ira2D and pde2D mutants do not tolerate the loss of mtDNA (Dunn et al 2006). This suggests that the hyperactivation of Ras2 or the elevated levels of cAMP are not tolerated in respiratory-deficient strains.…”
Section: Discussionmentioning
confidence: 99%
“…The highest-scoring predicted difference between CAB115/1-2 and its parent strain CAB115 was in a previously identified (Dunn et al 2006) gene, MGR1. Sequence analysis of MGR1 revealed a G-to-T transversion at nucleotide 778, resulting in a premature stop at codon 261 (of 417), termed mgr1-1.…”
Section: Resultsmentioning
confidence: 99%
“…The Mgr1 and Mgr3 proteins have recently been shown to associate with each other and with Yme1 (Dunn et al 2006(Dunn et al , 2008, the inner mitochondrial membrane AAA ATP-dependent zinc protease (Nakai et al 1995;Pearce and Sherman 1995;Weber et al 1996) facing the intermembrane space (Leonhard et al 1996). These newly discovered subunits of the i-AAA complex bind to known Yme1 substrates and are required for normal degradation rates in vivo, suggesting that they recruit substrate proteins to Yme1 for degradation (Dunn et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation